In Silico Assessment of Safety and Efficacy of Screw Placement for Pediatric Image-Guided Otologic Surgery - Hermann, Jan; Mueller, Fabian; Weber, Stefan; Caversaccio, Marco; O'Toole Bom Braga, Gabriela (Frontiers in Surgery, 2021)
Introduction: Current high-accuracy image-guided systems for otologic surgery use fiducial screws for patient-to-image registration. Thus far, these systems have only been used in adults, and the safety and efficacy of the fiducial screw placement has not yet been investigated in the pediatric population. Materials and Methods: In a retrospective study, CT image data of the temporal region from 11 subjects meeting inclusion criteria (8-48 months at the time of surgery) were selected, resulting in n=20 sides. These datasets were investigated with respect to screw stability efficacy in terms of the cortical layer thickness, and safety in terms of the distance of potential fiducial screws to the dura mater or venous sinuses. All of these results are presented as distributions, thickness color maps, and with descriptive statistics. Seven regions within the temporal bone were analyzed individually. In addition, four fiducial screws per case with 4 mm thread-length were placed in an additively manufactured model according to the guidelines for robotic cochlear implantation surgery. For all these screws, the minimal distance to the dura mater or venous sinuses was measured, or if applicable how much they penetrated these structures. Results: The cortical layer has been found to be mostly between 0.7 – 3.3 mm thick (from the 5th to the 95th percentile), while even thinner areas exist. The distance from the surface of the temporal bone to the dura mater or the venous sinuses varied considerably between the subjects and ranged mostly from 1.1 – 9.3 mm (from the 5th to the 95th percentile). From all 80 placed fiducial screws of 4 mm thread length in the pediatric subject younger than two years old, 22 touched or penetrated either the dura or the sigmoid sinus. The best regions for fiducial placement would be the mastoid area and along the petrous pyramid in terms of safety. In terms of efficacy, the retrosigmoid followed by the petrous pyramid, and infrasigmoid regions are most suited. Conclusion: The current fiducial screws and the screw placement guidelines for adults are insufficiently safe or effective for pediatric patients.